Proposal evaluation and continuous improvement of the Business Management System of the Institute of Animal Science (Visión Empresarial, 2018)
Commercial System Management Institute of Animal Science is evaluated applying a Model of Business Excellence from the results derived from a rigorous and extensive literature review on modern theories and approaches associated with trade and business management, as well as methodologies that allowed for an assessment systemic, multifactorial and inclusive, corresponding to the narrow natural link between the evaluated activity and business management of an organization. ItÂ´s applied the European Model of Business Excellence, which allowed the characterization with a great level of detail the main deficiencies associated with Leadership, Policy and Strategy, Resource Management, Human Capital and Processes, staff satisfaction and Customers, and Business Results Impact on Society, which do not favor an appropriate commercial management the products of science in the institution. Moreover, they applied specially designed by the author surveys that complement and extend the study to achieve the objectives. We show that the current conception of the organizational structure and management system ICA business does not contribute to effective marketing products and services mentioned the absence of a specialized team, with defined responsibilities and its own budget, to ensure the link naturally between the market and researchers; hence, the need for ensure the new conception the natural link between the functions of the researchers and business managers; the first, as responsible to ensure the scientific characteristics - technical products and services; the second, of all those linked to the security and safety marketing. At the same time, measures and means proposed for the improvement of the evaluated system, ranging from a proposed structure for commercial management system, to theoretical concepts and practical applications.
Keywords: EFQM model, Business Management, Sales Management, Evaluation